Different rs-fMRI Data Processing Methods in the Study of Vascular Cognitive Impairment - Ying GUAN; Luwen ZHU; Feng WANG; Danna CAO; Xiaoling LI; Qiang TANG (康复学报)
Vascular cognitive impairment(VCI)refers to dementia associated with small vessel damage caused by long-term hypertension, diabetes, hyperlipidemia and other cerebrovascular risk factors. With the aging of the population, the incidence of VCI is increasing year by year. About 40%of patients with cerebrovascular disease will have cognitive impairment, which can be expressed in different degrees of memory, language and visual space ability, and affect patients'daily activities, social interaction activities and work ability severely. VCI has become the second largest type of dementia after Alzheimer's disease, which has placed a heavy burden on society and families. If it can be detected early and treated in time, it can effectively improve prognosis of patients with VCI.Resting state functional magnetic resonance imaging(rs-fMRI)is a spontaneous neuronal activity in different brain regions at rest in a resting state where the subject is quiet, lying, without movement, closed eyes or blinking, but does not enter sleep and has no systemic thinking activity. Establish a network and functional connection between the relevant brain regions to reflect the spontaneous functional activities of the brain at rest. Generalized rs-fMRI includes blood oxygen level-dependent functional magnetic resonance imaging, magnetic resonance spectroscopy, magnetic susceptibility weighted imaging, and diffusion tensor imaging. Narrowly defined rs-fMRI refers to blood oxygen level-dependent functional magnetic resonance imaging. The technique mainly reflects the spontaneous activity of neurons by reflecting the spontaneous activity of the brain's blood oxygen level-dependent signal, which is closer to the physiological state than the task-state functional magnetic resonance imaging. As a sensitive auxiliary examination method, rs-fMRI has been widely used in the neurological mechanism and diagnosis and treatment of VCI.In clinical application, there are many methods of rs-fMRI data processing for VCI, such as amplitude of low-frequency fluctuation(ALFF), regional homogeneity(ReHo), functional connectivity(FC), brain network, etc. Different data processing methods have different meanings, advantages and disadvantages, and application value, and different data processing and analysis methods have some differences in the results, such as ALFF and ReHo, which belong to the analysis method of local functional activity characteristics; functional connectivity and brain network belong to linear correlation analysis method. This article have reviewed the research on the state of rs-fMRI in the field of VCI in recent years, and summarized the commonly used rs-fMRI data processing methods and features. The application of different functional data processing methods of magnetic resonance in VCI aims to provide imaging evidence for the clinical diagnosis and treatment of VCI.